Contribution of BCR-ABL kinase domain mutations to imatinib mesylate resistance in Philadelphia chromosome positive Malaysian chronic myeloid leukemia patients - Elias, Marjanu Hikmah; Baba, Abdul Aziz; Husin, Azlan; Abdullah, Abu Dzarr; Hassan, Rosline; Goh, Ai Sim; Abdul Wahid, S. Fadilah; Ankathil, Ravindran (PAGEpress, 2012)
Development of resistance to imatinib mesylate (IM) in chronic myeloid leukemia (CML) patients is mediated by different mechanisms that can be classified as BCR-ABL dependent or BCR-ABL independent pathways. BCR-ABL dependent mechanisms are most frequently associated with point mutations in tyrosine kinase domain (TKD) of BCR-ABL1 and also with BCR-ABL gene amplification. Many different types and frequencies of mutations have been reported in different studies, probably due to the different composition of study cohorts. Since no reports are available from Malaysia, this study was undertaken to investigate the frequency and pattern of BCRABL kinase domain mutations using dHPLC followed by sequencing, and also status of BCR-ABL gene amplification using fluorescence in situ hybridization (FISH) on 40 IM resistant Malaysian CML patients. Mutations were detected in 13 patients (32.5%). Five different types of mutations (T315I, E255K, Y253H, M351T, V289F) were identified in these patients. In the remaining 27 IM resistant CML patients, we investigated the contribution made by BCR-ABL gene amplification, but none of these patients showed amplification. It is presumed that the mechanisms of resistance in these 27 patients might be due to BCRABL independent pathways. Different mutations confer different levels of resistance and, therefore, detection and characterization of TKD mutations is highly important in order to guide therapy in CML patients.